Nano Sponge: A Beneficial Targeted Drug Delivery System - Kolhe, Nitin; Shirsekar, Prathmesh; Deshmukh, Mansi; Shinde, Shankar (Current Nanomedicine, 2025)
Global scientists are facing problems regarding targeting an analyte to a predetermined receptor, enhancing drug release, improving patient compliance, and improving absorption of the drug to be administered. The invention of a new compound known as nano sponges can nullify this issue. The structure of nano sponges is similar to that of minute sponges, which are measured in nanometers and can be used as a carrier for selected drugs. The job of these sponges is to pass through the bloodstream until it is transported towards the intended destination and a receptor. The metabolism of the drug should be controlled with the help of nanosponges. The first thing to remember while formulating encapsulated nanosponges is that the drug should be partially or slightly soluble in the vehicle, not entirely. Nanosponges are also used for improving solubility, and bioavailability, and decreasing skin irritation from the drug. The studies are going on nanosponges to be an effective gas carrier because of their highly porous nature. Nanosponges can be formulated as liquids, powders, gels, ointments, and creams, as well as possibly administered by mouth, epidermis, and intravenous routes. Thus, nanosponge technology delivers drugs to a specific site and extends drug release, thereby increasing patient compliance.
Keywords: Nanosponges